2017
DOI: 10.1515/nanoph-2017-0025
|View full text |Cite
|
Sign up to set email alerts
|

Reversible thermochromic response based on photonic crystal structure in butterfly wing

Abstract: Subtle responsive properties can be achieved by the photonic crystal (PC) nanostructures of butterfly based on thermal expansion effect. The studies focused on making the sample visually distinct. However, the response is restricted by limited thermal expansion coefficients. We herein report a new class of reversible thermochromic response achieved by controlling the ambient refractive index in butterfly PC structure. The photonic ethanol-filled nanoarchitecture sample is simply assembled by sealing liquid eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…And the bending caused the periodicity of the photonic crystal to change and produced a color change. Wang et al reported a new class of reversible thermochromic responses achieved by controlling the refractive index of the environment in a butterfly PC structure . Photon ethanol‐filled nanostructured samples were simply assembled by encapsulating liquid ethanol‐filled butterfly wings.…”
Section: Functional Components Of Stimesmentioning
confidence: 99%
“…And the bending caused the periodicity of the photonic crystal to change and produced a color change. Wang et al reported a new class of reversible thermochromic responses achieved by controlling the refractive index of the environment in a butterfly PC structure . Photon ethanol‐filled nanostructured samples were simply assembled by encapsulating liquid ethanol‐filled butterfly wings.…”
Section: Functional Components Of Stimesmentioning
confidence: 99%
“…2 Examples of thermochromic materials include liquid crystals, 3,4 photonic crystals, 5 gold or silver nanoparticles, 6 leuco dye systems, 7 polydiacetylene derivatives 8 and aggregachromic dyes. 9 Bragg reflection, 5,10 surface plasmon absorption 6 , ring-opening and closing of molecular structures, 7 protonation and deprotonation of dye materials 11 or conformational stretching of spiral structures 4 have been used to explain the mechanisms of these thermochromic materials. Nevertheless, few reports mention the relative toxicity of these thermochromic materials and concern about their safety limits their application in the areas of food or health care products packaging.…”
Section: Introductionmentioning
confidence: 99%
“…reported a novel thermal sensing platform based on the structure of Papilio ulysses butterfly. In this work, the P. ulysses butterfly wings sealed liquid ethanol are made into liquid ethanol filling photonic crystal (LEF‐PC) [ 43 ] ( Figure d,e). The nanostructure of P. ulysses butterfly wing is different from the Pagoda‐shaped nanostructure of Morpho butterfly mentioned above ( Figure a).…”
Section: Bioinspired Optical Sensorsmentioning
confidence: 99%
“…f) Color response with different temperatures changed by contacting a finger, contact time is from 0 to 5 s. Reproduced with permission. [ 43 ] Copyright 2017, De Gruyter.…”
Section: Bioinspired Optical Sensorsmentioning
confidence: 99%